2016
DOI: 10.1111/odi.12488
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with oral potentially malignant disorders in Brazil's rural workers

Abstract: Rural workers showed high vulnerability to the presence of OPMDs, as estimated prevalence exhibited was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
44
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 25 publications
8
44
3
4
Order By: Relevance
“…Significant association with ageing has been present in other studies (19,21,22) confirming that accumulation of sun exposure is the main risk factor for AC. This statement is further corroborated by the significant correlation between AC and outdoor working for more than 25 years (OR 7.14), being the relation with accumulated time of UV exposure also reported by other authors (18,19,22,23,25). Fitzpatrick phototype II was significantly related to AC presence (OR 2.94); this is coherent with previous AC prevalence studies that found a significant correlation with light/fair skin or white/Caucasian race (18)(19)(20)(21)(22)(23)25).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Significant association with ageing has been present in other studies (19,21,22) confirming that accumulation of sun exposure is the main risk factor for AC. This statement is further corroborated by the significant correlation between AC and outdoor working for more than 25 years (OR 7.14), being the relation with accumulated time of UV exposure also reported by other authors (18,19,22,23,25). Fitzpatrick phototype II was significantly related to AC presence (OR 2.94); this is coherent with previous AC prevalence studies that found a significant correlation with light/fair skin or white/Caucasian race (18)(19)(20)(21)(22)(23)25).…”
Section: Discussionsupporting
confidence: 84%
“…The rest of the analysed variables were not significant. Sex distribution showed a high proportion of females in both the screening and the AC population (59.1% and 55.4%, respectively) and this could be related to the higher tendency of women to seek dermatological consultation compared with men (30); in contrast, other AC prevalence studies showed a clear superiority of men (15,16,18,19,23,25) and the reasons the authors gave for that finding were that women often use lipsticks providing a physical block against UV radiation, have a bigger tendency to use a sunscreen and are less frequently engaged in outdoor activities. Furthermore, an important percentage of the AC prevalence studies were performed in specific populations with professional activities that clearly have a male predominance (fishermen, sugar cane collectors, farmers, rural workers).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In general population samples outside the hospital environment, the prevalence is found to be lower. Among 1241 individuals (47.1% women) in India, the prevalence of erythroplakia was 0.24% (Kumar et al., ), and a similar prevalence (0.3%) was found among 1385 rural Brazilian workers, of which 53.2% were females (Ferreira et al., ).…”
Section: Prevalencementioning
confidence: 89%